PENGARUH GAYA DAN MOTIVASI TERHADAP HASIL BELAJAR MARKETING KELAS X PEMASARAN SMK IMMANUEL - Ansela Ansela; Achmadi Achmadi; Husni Syahrudin (Universitas Tanjungpura, 2017)
Abstract The purpose of this research was to know the influence of the influence of learning style and learning motivation on students’ learning result in subject on tenth grade students of SMK Kristen Immanuel II Sungai Raya. The method used in this research was descriptive-quantitative. This is a correlation research. The number of the sample is 68 students. The data was collected by using indirect communication technique (influence of learning style and learning motivation-questionnaire), direct communication technique (directive interview) and direct observation technique (directive observation). The result of this research showed that there is the positive influence of the influence of learning style to the learning motivation of the tenth grade students of SMK Kristen Immanuel II Sungai Raya It is indicated by the number 2,746 which showed that there is an influence of the independent variable to dependent variable. When it is compared with T table on the significance level of 0,05 at 1998. So it is greater than T table or 2,746 > 1,998, so Ha is accepted and Ho is rejected. The magnitude of the influence of adversity quotient on student motivation by 29,3% while the rest influenced by other factors are not described in this study. So the conclusion is the adversity quotient has significant impact on the learning motivation of the students the tenth grade students of SMK Kristen Immanuel II Sungai Raya. Keywords: learning style, Learning Motivation, learning result